Anticipating Parenthood Among Lesbian, Gay, Bisexual, and Heterosexual Young Adults Without Children in Portugal: Predictors and Profiles - Gato, Jorge; Leal, Daniela; Coimbra, Susana; Tasker, Fiona (Frontiers in Psychology, 2020)
Parenthood is a highly valued life goal, independent of one’s sexual orientation. However, the majority of studies exploring young adults’ parenthood plans have relied exclusively on samples of heterosexual individuals. This study aimed (i) to explore differences in parenthood intentions as a function of sexual orientation, (ii) to investigate to what extent sociodemographic and psychological characteristics predict parenthood intentions of lesbian, gay, bisexual (LGB), and heterosexual individuals, (iii) to test the mediating effect of stigma between sexual orientation and parenthood intentions, and (iv) to identify and characterize profiles of prospective parenthood (through cluster analysis). Data were gathered using an online survey from 375 self-identified LGB and heterosexual young adults without children in Portugal, with a mean age of 25.83 years old (SD = 4.49). Findings indicated that LGB individuals were less likely to intend to have children than heterosexual individuals; furthermore, among LGB individuals, lesbian women expressed stronger intentions to have children than did gay men. Similarities between heterosexual and LGB young adults were observed concerning the psychological determinants of parenthood intentions. Four distinctive profiles of prospective parenthood were identified: aspiring parents not anticipating stigma, aspiring parents anticipating stigma, childfree intent, and childfree ambivalent. Lesbian and bisexual women mostly populated the childfree ambivalent cluster; in contrast, the aspiring parents anticipating stigma cluster contained an overrepresentation of men, including sexual minority men. Professionals may want to attend to communalities and specificities of prospective parenthood as a function of sexual orientation, in order to provide unbiased and culturally competent support to sexual minority individuals.